Geometric parameters and response surface methodology on cooling performance of vortex tubes. Issue 9 (21st October 2017) - Nouri-Borujerdi, A.; Bovand, M.; Rashidi, S.; Dincer, K.
ABSTRACT: This research has investigated the effect of certain geometric parameters on cooling performance of three vortex tubes. The influencing parameters include three length/diameter ratios L / D  = 10, 25, 40, three nozzle cases and each case with number n  = 2, 4, 6 nozzles, three cold orifice/diameter ratios β  = 0.389, 0.5, 0.611 and three inlet pressures Pi  = 2, 2.5 and 3 bar. The experiments are conducted based on three factors, two-level and central composite face-centred design with full factorial. The results are analysed according to the principle of response surface methodology. The goodness of fit of the regression model is inspected using the analysis of variance and F -ratio test. The values of R 2 and R 2 -adjusted are close to 100% which show a very good correlation between the observed and predicted values. The results show that the effect of number of nozzles on the energy separation depends on the L / D values.